United States Pulmonary Hypertension Scientific Registry (USPHSR): rationale, design, and clinical implications. (1st May 2019) - Elliott, C. Gregory; Austin, Eric D.; Badesch, David; Badlam, Jessica; Benza, Raymond L.; Chung, Wendy K.; Farber, Harrison W.; Feldkircher, Kathy; Frost, Adaani E.; Poms, Abby D.; Lutz, Katie A.; Pauciulo, Michael W.; et al.
Abstract : Diagnostic World Health Organization (WHO) Group 1 pulmonary arterial hypertension (PAH) and Diagnostic Group 1′ pulmonary veno‐occlusive disease (PVOD) and/or pulmonary capillary hemangiomatosis (PCH) are progressive and fatal disorders. Past registries provided important insights into these disorders, but did not include hormonal exposures or genomic data. The United States Pulmonary Hypertension Scientific Registry (USPHSR) will provide demographic, physiologic, anorexigen and hormone exposure, genomic, and survival data in the current therapeutic era for 499 patients diagnosed with PAH, PVOD, or PCH. The USPHSR also will explore the relationship between pharmacologic, non‐pharmacologic, and dietary hormonal exposures and the increased risk for women to develop idiopathic or heritable PAH.